O uso de evidências em macroeconomia: Notas históricas e metodológicas - Maurício Mota Saboya Pinheiro; Lucas Trentin Rech; Jo\~ao Cláudio Basso Pompeu (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
The aim of this paper is to shed light on some conceptual, methodological and historical aspects about the use of evidence in Economics and, in particular, in Macroeconomics. We seek to pave the way for a deeper understanding about the normative criteria to guide the good use of evidence in macroeconomic policies. The text seeks to answer the following questions: i) To which networks or types of statements (hypotheses, models, theories, etc.) does the criterion of empirical adequacy in economic science apply?; ii) How does the formalization of language and the measurement of economic magnitudes affect the role of evidence in scientific progress in Economics? iii) How do the criteria of assessment of empirical adequacy vary according to schools of thought in Economics?; iv) what contextual factors (historical, ideological, political, etc.) could condition economists' choices with respect to those sets of statements?; v) How is the concept of causality in economics elucidated and how can a methodologically pluralistic orientation towards causality serve macroeconomic policy decisions?; and vi) What lessons can the methodology and history of economic thought give to the governance of the use of evidence for macroeconomic policies? More than pointing to a single solution to the problem of evidence governance in macroeconomic theory and policy, this text invites us to a pluralistic attitude - though moderate - regarding: i) the concept of evidence in Economics; ii) the empirically assessable unity in economic theory and policy; iii) the concept of causality involved in theoretical and practical analyzes in macroeconomics.
Keywords: B41; 330; philosophy of science; Economics; economic methodology; causality; evidence-informed policymaking; macroeconomic policies